Workshop on the use of GeoGebra as a visualization media of construction of flat shape area formula - Muhammad Ridlo Yuwono; Triyono Triyono; Septiana Wijayanti; Tasari Tasari; Joko Sungkono; Fika Aisyah Munif; Anita Setiyaningsih (Community Empowerment, 2023)
The purpose of this community service is to train junior high school mathematics teachers to be able to utilize GeoGebra in visualizing the construction of flat shape area formula. The program carried out in collaboration with IndoMS DIY-Central Java. The method used in this community service is an online workshop. The result of this workshop is that the participants are able to visualize the construction of flat shape area formula for a triangular and parallelogram.